СВОЕОБРАЗИЕ ИНДИВИДУАЛЬНО-АВТОРСКОГО СТИЛЯ ПИСАТЕЛЯ Т.МУРАДА (на материале романа «Поле, унаследованное от отца) (Scientific journal of the Fergana State University, 2023)
This article considers the question of stylistic orientation, which is observed in the creative individuality of the writer Togay Murad.